A new species of Dinotoperla Tillyard, 1921 from the Shoalhaven Catchment, New South Wales, Australia (Plecoptera: Gripopterygidae) - Theischinger, Gunther; Mynott, Julia H. (Zootaxa, 2019)
Dinotoperla cherylae sp. nov. (Holotype ♂: New South Wales, Upper Kangaroo River, 34.672998oS/150.601391oE, 14-Dec-2017) is described from the Shoalhaven Catchment in New South Wales, Australia. The affinities and phylogenetic relationships of the new species are discussed.